EUCALYPTUS WOOD RESIDUES DERIVING FROM SAWMILLS FOR PARTICLEBOARD MANUFACTURING - IWAKIRI, Setsuo; da CUNHA, Alexandro Bayestorf; ALBUQUERQUE, Carlos Eduardo Camargo; GORNIAK, Elianice; MENDES, Lourival Marin (Scientia Agraria, 2000)
This research paper was developed aiming to evaluate the feasibility of utilization of the woods of Eucalyptus maculata, E. grandis and E. tereticornis, deriving from saw mill processing residues to particleboard manufacture. Was manufactured 24 boards, being eight treatments, defined in function of three species and its mixture, and two resin levels (8 and 12%). The processing variables were: board density = 0,75g.cm-3, press temperature = 140° C, pressing time = 8 min and pressure = 40 kg.cm-2. The following physical and mechanical properties were evaluated: water absorption (AA-2 and 24 h), thickness swelling (IE-2 and IE24 h), internal bond (LI), modulus of elasticity (MOE) and modulus of rupture (MOR) in bending strenght. Boards manufactured with these eucaliptus species showed satisfctory physical and mechanical properties in comparison to some referentials species as Pinus elliottii, Mimosa scabrella and Eucalyptus dunnii presented in the literature. The boards manufactured with 12% of resin level showed better results than boards with 8%. Based in the mechanical properties, the Eucalyptus maculata showed the best behavior for particleboard manufacture.